Impreactory Psalms Dalam Konteks Ancient Near East (ANE) Dan Perjanjian Lama - Winardi Tarigan (Predica Verbum: Jurnal Teologi dan Misi, 2024)
Expressions of revenge or curses against enemies in psalms are often called imprecatory psalms. In investigating psalm texts containing curses, experts usually relate them to the Ancient Near East (ANE) cultural background and several texts in the Old Testament as the basis or reference. This research will explore the relationship between imprecise Psalms and the tradition of curses in ANE culture and the practice of curses in the Old Testament outside the Psalms. So, it will provide a comprehensive contribution to evaluating imprecise psalms in the context of the ANE and Old Testament. Are the curses in the three contexts the same or have significant differences? The author attempts to review and evaluate curses in these three contexts through descriptive studies, literature reviews, contextual analysis, and comparative studies. While there are influences and similarities in the use of curses between Psalms and ANE cultures and the Old Testament, it cannot be avoided that there are also differences that need to be considered to understand the context and purpose of the use of curses in the psalms. Interpreters must highlight the differences in genre, meaning, and essence between curses in the context of the ANE and the Old Testament and the imprecatory psalms. However, considering this background in interpretation will broaden the understanding and insight into the imprecatory in the context of modern Christianity.